Assessment of the application for renewal of authorisation of GalliPro® (Bacillus subtilis DSM 17299) for chickens for fattening. (16th April 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: GalliPro ® is the trade name for a feed additive based on viable cells of a strain of Bacillus subtilis intended for use as a zootechnical additive (gut flora stabiliser) in feed for chickens for fattening. The product is currently authorised for use in chickens for fattening. This opinion concerns the renewal of this authorisation. Bacillus subtilis is considered by EFSA to be suitable for the qualified presumption of safety (QPS) approach to establish the safety for the target species, consumers and the environment. The identity of the strain present in the additive was established and evidence was provided on the lack of toxigenic potential as well as acquired antibiotic resistance determinants to antibiotics of human and veterinary importance. Accordingly, this strain is presumed safe for the target species, consumers of products derived from animals fed the additive and the environment. Since no concerns are expected from other components of the additive, GalliPro ® is considered safe for the target species, consumers and the environment. The applicant has provided evidence that the additive currently in the market complies with the existing conditions of authorisation. The FEEDAP Panel confirms its previous conclusions that GalliPro ® is safe for the target species; consumers of products from animals fed the additive and the environment. GalliPro ® should be considered a potential respiratory sensitiser. In the absence of data, the FEEDAP Panel cannot conclude on the potential of GalliPro ® for skin and eyes irritancy and dermal sensitisation.